Capacitating Teachers’ Research Skills Through Collaborative Action Research Buddies - Bongcayao , Anafe A. (Future Science / FSH-PH Publications, 2023)
Action research is a valuable tool for personal and professional development. It allows teachers to assess their teaching practices, reflect on learning outcomes, and generate practical ways of improving their pedagogical competence. Consequently, it results in positive educational impact, such as increased academic performance and school effectiveness. Hence, this action research study aimed to capacitate the teachers of Kinan-oan Elementary School, Trinidad II District, Trinidad, Bohol S.Y. 2021-2022 through Collaborative Action Research Buddies – an approach that aimed to empower, retool, train, and foster action research skills. As an intervention to the difficulties encountered by teachers in conducting research, the researchers conducted a Capacity Building on Enhancing Teachers’ Action Research Skills through Collaborative Action Research Buddies among the thirteen (13) teachers of the said school. This study employed descriptive statistics and individual interview to track the improvement of the teachers before and after undergoing the said intervention. The results showed an improvement in their capacity to undertake a research project, as shown by the increased number of teachers who could craft an action research proposal based on required standards. Interestingly, all participants were able to carry out their action research proposals and had produced completed action research manuscripts. Based on the participants’ narratives, they attributed this success to the intensive training they underwent that targeted their weaknesses and deficiencies in research writing. This result implies that Collaborative Action Research Buddies, as a strategy, could enhance teachers’ action research skills through its facilitative effect on their cognitive and affective domains. Hence, it is recommended that Collaborative Action Research Buddies be implemented in Trinidad II District to help the teachers from other schools improve their competence in crafting a research proposal and conducting it based on a specified timeline. However, further research is needed to identify other factors that could motivate and help teachers improve their competence in undertaking classroom-based action research.